2023
DOI: 10.21873/invivo.13265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Nutritional Status on Long-term Survival in Patients With Stage I-III Colorectal Cancer

Abstract: Background/Aim: In addition to oncological and treatment factors, the outcomes of cancer treatment are greatly influenced by host factors, such as the nutritional status. The aim of this study was to evaluate the association between the preoperative nutritional status and the prognosis of colorectal cancer patients using three nutritional indices. Patients and Methods: The target cohort consisted of 529 patients with stage I-III colorectal cancer, who underwent curative surgery between January 2015 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In gastric cancer, it has been reported that improved preoperative nutritional status contributes to fewer postoperative complications and shorter hospital stays (3,23). In colorectal cancer and liver metastases of colorectal cancer, preoperative nutritional status has also been reported to influence postoperative complications and survival (24)(25)(26)(27), and to be a predictor of recurrence and poor prognosis in elderly patients with rectal cancer undergoing radical resection after preoperative chemotherapy (neoadjuvant chemotherapy) (28). Therefore, we believe that GNRI, a useful method of assessing nutritional status, is a factor that influences the duration of surgery and cancer chemotherapy treatment in gastric and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, it has been reported that improved preoperative nutritional status contributes to fewer postoperative complications and shorter hospital stays (3,23). In colorectal cancer and liver metastases of colorectal cancer, preoperative nutritional status has also been reported to influence postoperative complications and survival (24)(25)(26)(27), and to be a predictor of recurrence and poor prognosis in elderly patients with rectal cancer undergoing radical resection after preoperative chemotherapy (neoadjuvant chemotherapy) (28). Therefore, we believe that GNRI, a useful method of assessing nutritional status, is a factor that influences the duration of surgery and cancer chemotherapy treatment in gastric and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%